LEGAL PROTECTION FOR CUSTOMER SEGREGATED ACCOUNT OWNER FROM LOSS DUE TO THE BANKCRUPTY OF FUTURES BROKERAGE FIRM - Yessy Meryantika Sari (Jurnal Dinamika Hukum, 2016)
Commodity futures trading is a business activity that is complex and involves many parties including Client Segregated Account and Brokerage Company. This business promises huge benefits but ba-lanced with a high risk of loss. Therefore, a potential event of bankruptcy. Customer as the owner of the funds which mandated funds to the brokerage company to be managed for purposes of the transaction, should get legal protection from potential losses due to bankruptcy of futures brokerage firm. The spirit of the law in protection for customers is reflected in the preamble of le-gal norms futures trading as further elaborated in the general legal provisions stipulated in the Fu-tures Trading Act.Keywords : Legal Protection, Customer Segregated Account Owner, Broker, Bankruptcy Law.